Optimalisasi Pelayanan Publik melalui Aplikasi SIPAKU di Kecamatan Kiaracondong - Gilbert Aditya; Maharani Suryaningsih Imanto; Ardieansyah Ardieansyah (Jurnal Teknik Informatika dan Teknologi Informasi, 2025)
The advancement of information technology has compelled government institutions to undergo digital transformation as a means of enhancing the effectiveness and efficiency of public services. As citizens increasingly demand fast, accessible, and transparent administrative processes, digitalization has become a necessary strategy. One such initiative is undertaken by the Kiaracondong Subdistrict through the development of SIPAKU (Integrated Administrative Services Information System), a digital platform designed to facilitate online civil administration services such as ID card applications, family registration, moving letters, and other administrative documents. This study aims to evaluate the extent to which SIPAKU has optimized public service delivery at the subdistrict level and to identify the key enabling and inhibiting factors affecting its implementation. The study applies a qualitative descriptive method with data collected through direct observation at the subdistrict office, informal interviews with civil servants, and documentation of the SIPAKU system in use. The findings reveal that SIPAKU has improved service accessibility for the public, accelerated administrative procedures, and enhanced bureaucratic transparency and accountability at the local level. However, the system also faces several challenges, including limited digital literacy among residents, inadequate technological infrastructure, and insufficient public outreach regarding the application’s use. This study recommends the full integration of SIPAKU with broader civil registration databases, intensive training for administrative personnel, and the development of inclusive communication strategies to ensure equitable access to digital services across all community groups.